Increased Yield and High Resilience of Microbiota Representatives With Organic Soil Amendments in Smallholder Farms of Uganda - Köberl, Martina; Kusstatscher, Peter; Wicaksono, Wisnu Adi; Mpiira, Samuel; Kalyango, Francis; Staver, Charles; Berg, Gabriele (Frontiers in Plant Science, 2022)
Organic matter inputs positively affect soil fertility and quality but management effects on the soil and plant microbiome are less understood. Therefore, we studied the response of microbial colonization of the East African highland banana cultivar ‘Mpologoma’ (AAA genome) under different mulch and manure treatments on three representative smallholder farms in Uganda. In general, the gammaproteobacterial community appeared stable with no significant response to organic matter inputs after 24 months of treatment. Significant differences (P<0.05) in the plant-associated carpo-, phyllo- and rhizosphere microbial community composition and diversity were found among individual sampled farms, independent of added soil inputs. Across farms, banana fruit harbored a richer and more balanced gammaproteobacterial community than the rhizo- and endospheres. Gammaproteobacterial beta diversity was shaped by microenvironment (44%) as well as sampling site (4%). Global effects of treatments in the rhizosphere analyzed using Linear discriminant analysis Effect Size (LEfSe) showed significantly enriched genera, such as Enterobacter, under manure and mulch treatments. As shown in previous works, bunch size and total yield were highly increased with manure and mulch, however, our results highlight general short-term microbial stability of Ugandan banana cropping systems with increases in the gammaproteobacterial community.